SINKRONISASI MUHKAM DAN MUTASYABIH - ., Parhan . (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2024)
Discussions about the Muhkam and Mutasyabih verses never stop because of the extensive content of the Al-Qur'an in understanding these verses in their entirety. Meanwhile, one of the factors that causes differences of opinion in understanding the Muhkam and Mutasyabih verses is the way of viewing verses that are clear (muhkam) and those that are still vague (mutasyabih). This research uses a qualitative approach and uses literature study as an approach. By using this method, it will be easier for writers to study and solve problems from various sources whose credibility is recognized. These sources include published books and well-known journal articles. The results of the research show that interpreting the muhkam verses in the Koran is sufficient with interpretation. However, if it is related to the mutasyabih verses, this requires deeper study because of the vagueness of the verse.